Evaluating the Benefits of a Tele-Exercise Program on Quality of Life and Body Composition Among Female Older Adults - Khanthong, Phaksachiphon; Sangprapai, Warinee; Jetinai, Kotchakorn; Namboonlue, Chaiyawat (Physical Education Theory and Methodology, 2024)
Objectives. This study aimed to assess the impact of an 8-week tele-exercise program on the quality of life (QoL) and body composition among female older adults. Materials and methods. This study involved female participants aged 60 and older, using a quasi-experimental research design. The tele-exercise regimen comprised a multimodal approach, with sessions lasting 30 minutes, conducted three times a week over an 8-week period. The program included breathing exercises, cognitive training, balance exercises, strength training, stretching, aerobic dance and karaoke singing. The sessions were conducted via streaming studio facilities at the Computer Center of Ubon Ratchathani Rajabhat University (Thailand). The tele-exercise equipment was represented by the following technical means: a 50-inch LED TV, OBS (Open Broadcaster Software) version 30.1.2 for live broadcasting and video recording, Google Meet for virtual interaction, wireless portable microphones, a desktop computer, and two 19-inch computer monitors. Pre- and post-intervention data were collected, including assessments of QoL using the Thai abbreviated version of the World Health Organization Quality of Life questionnaire and body composition measurements (waist circumference and bioelectrical impedance analysis; BIA). Results. Statistically significant improvements were observed in both QoL and body composition following the tele-exercise intervention. QoL scores demonstrated significant enhancements in overall QoL (p = 0.004), as well as in the social relationship (p = 0.002) and environmental (p = 0.001) domains. Regarding body composition, reductions in waist circumference and visceral adipose tissue were statistically significant (p < 0.05), while muscle mass and body fat mass showed trends toward improvement, though not statistically significant. Conclusions. The findings suggest that tele-exercise training holds promise for enhancing QoL and positively influencing body composition among female older adults. This underscores the potential of tele-exercise as a viable option for older adults, offering cost and time-saving benefits, particularly in situations where transportation may pose challenges.